PENGARUH MANAJEMEN LABA TERHADAP KINERJA KEUANGAN PERUSAHAAN MELALUIGCG SEBAGAI VARIABEL MODERATING - Nurma Risa; Sukaesih Sukaesih (JRAK: Journal of Accounting Research and Computerized Accounting, 2014)
The purpose of this research are to verify the impact of earning management to financial performance with good corporate governance as a moderating variable. Number of commissioner board and the existence of auditcommittee are use to indicate good coporate governance. The sample of research is manufacturing company thatlisted in Bursa Efek Indonesia for the year 2009 – 2011. T-test is used to prove all of hypothesis. The results indicatethat earning management have an impact to company financial performance. Number of commissioner board can beweaken the impact of earning management to company financial performance, but the other hand, existence of auditcommittee can not.